Renal Toxic Effects of MgO NPs in Male Rats - Shafiq, Ayser Abdullah; Luaib, Noori Mohammed; Mahdi, Raghad Harbi; Alsaimary, Ihsan Edan (Iraqi Journal of Science, 2024)
Engineered nanomaterials are so tiny that they cannot be seen without special equipment; they are found in many industrial products today, consumer products, medicines, and food products. The small size and other properties of nanomaterials can make them very hazardous to human health. Magnesium oxide nanoparticles (MgO NPs), or metal oxides, have several advantages compared to other metal oxide nanoparticles because of their properties. Therefore, multiple uses of MgO NPs put human health at risk from prolonged exposure. The study aimed to determine how treatment with oral doses of MgO nanoparticles affects the kidneys of male rats through the oral route at 250 and 1000 mg/kg for 14 days, 28 days, and 56 days, respectively. Sixty mature male rats (2.5–3 months) were divided randomly into twelve groups of six rats each and gavaged with MgO NPs. The results observed a significant increase (p<0.01) in urea, creatinine, and uric acid; the histopathological examinations demonstrated necrotic debris inside the lumen of renal tubules; debris of lining epithelial cells inside the lumen of renal tubules; and the marked renal tubules were non-functional focal areas of necrosis and apoptosis. MgO NPs demonstrate potential issues with the kidneys and human health.